ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA PADA STIE DWI SAKTI BATURAJA - Lilis Karnia; Yopi Yunsepa (STIE DWI SAKTI BATURAJA, 2021)
The purpose of this study is to determine the factors that affect student interest in entrepreneurship at STIE Dwi Sakti Baturaja. The method used in this research is descriptive and this research uses qualitative and quantitative analysis techniques. The results showed that based on the partial test there was an effect of entrepreneurship education (X1) and personality (X3) on the interest in entrepreneurship (Y) in STIE Dwi Sakti Baturaja students, while the family environment (X2¬) had no effect. Simultaneously there is the influence of entrepreneurship education (X1), family environment (X2¬), and personality (X3) on the interest in entrepreneurship (Y) in STIE Dwi Sakti Baturaja students.